SINTESIS SILIKA XEROGEL DARI ABU LIMBAH SEKAM PADI (Oryza sativa .L) DENGAN METODE SOL-GEL - Afryansyah Afryansyah; Chalesa Elmiya; Jihan Ghaisani (Jurnal Penelitian Sains, 2026)
Rice as the staple food for 90% of Indonesia's population, produces abundant unprocessed rice husk waste from processing, posing serious environmental threats. This research aims to convert the silica (SiO₂) content—ranging from 87%-97%—in rice husks into silica xerogel with significant economic potential through the sol-gel method. The synthesis involved several stages: preparation and calcination of rice husks, silica extraction using HCl and NaOH solutions to obtain sodium silicate, followed by neutralization to form silica hydrogel, and finally conversion into silica xerogel. The final product was analyzed through organoleptic tests, moisture content, and adsorption ability, where the organoleptic test results showed the physical form of weak solids (gel) on silica hydrogel, sandy grains on silica xerogel, as well as colorless and odorless on both. The moisture content of silica xerogel was 20%, compared to 10% in commercial silica gel. Meanwhile, adsorption testing revealed the percentage of adsorption ability of the synthesized silica was two times higher, which is 32.35% compared to the commercial one of 14.7%. It proved to be an effective short-term moisture adsorbent with significant absorption capability. This study highlights the potential of rice husk-derived silica xerogel as an effective, economical, and environmentally friendly alternative humidity adsorbent.